THE LOSS OF CREDITORS’ DROIT DE PREFERENCE (PRIORITY PRINCIPLE) DUE TO DEBTOR’S CORRUPT OFFENSES - Habib Adjie (International Journal of Latin Notary, 2022)
Creditors, as mortgage holders, are also entitled to the preeminent status of security in accordance with Droit de Preference as stated in the last sentence of Article 1 number 1 of Mortgage Law (UUHT), which gives priority to certain creditors over others. This mortgage characteristic is also mentioned in the last sentence of Article 20 paragraph (1) letter b, which stated that mortgage holders have privilege rights over other creditors. However, this status is disintegrated, assuming the debtors are involved in a corruption offense because their property becomes confiscated by court order despite being guaranteed to the creditor. Therefore, this condition fails to prioritize the Droit de Preference of the creditors with the implementation of the confiscation state, which needs to take precedence. In Article 19 paragraphs (2) and (3) of Law No. 31 regarding Eradication of Criminal Acts and Corruption, the legal remedy provided for creditors is only by submitting an Objection Letter to the court that imposed the confiscation without suspending the court's ruling. Such regulations tend to injure the goodwill creditors as well as abolish Droit the preference ability to provide legal protection and certainty toward creditors’ rights.